PENGGUNAAN UMPATAN PADA PLAYER GAME MOBILE LEGENDS - Tazqiyah Presty Laksita; Fitri Amilia; Yerry Mijianti (Jurnal Bastra (Bahasa dan Sastra), 2025)
The aim of this research is to describe forms based on references used by Mobile Legends players. This research uses qualitative research. This research data is in the form of words or phrases containing swear words based on the form of condition references, references to animal names, references to body parts, references to kinship, references to professions, references to activities, references to spirits, and references to objects. The data source used in this research is speech in the comments column that contains swear words, which has been provided by Moonton. The form of speech is taken from comments in the photo album provided, and also the message column in the Mobile Legends game. The data collection technique in this research is documentation in the form of listening and note-taking techniques. The data collection instrument used was the researcher himself. This research uses an extralingual matching method with a continuous contrast comparison technique. The application of the comparative technique in this research is that the researcher will compare the differences between the forms of swearing they use. In this case, data analysis is presented by describing the forms of swearing used by Mobile Legends Game Players.